Pancreas-Brain Crosstalk - Lkhagvasuren, Battuvshin; Mee-inta, Onanong; Zhao, Zi-Wei; Hiramoto, Tetsuya; Boldbaatar, Damdindorj; Kuo, Yu-Min (Frontiers in Neuroanatomy, 2021)
The neural regulation of glucose homeostasis in normal and challenged conditions involves the modulation of pancreatic islet-cell function. Compromising the pancreas innervation causes islet autoimmunity in type 1 diabetes and islet cell dysfunction in type 2 diabetes. However, despite the richly innervated nature of the pancreas, islet innervation remains ill-defined. Here, we review the neuroanatomical and humoral basis of the cross-talk between the endocrine pancreas and autonomic and sensory neurons. Identifying the neurocircuitry and neurochemistry of the neuro-insular network would provide clues to neuromodulation-based approaches for the prevention and treatment of diabetes and obesity.